2017
DOI: 10.3389/fpubh.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

Improving Access to, Use of, and Outcomes from Public Health Programs: The Importance of Building and Maintaining Trust with Patients/Clients

Abstract: The central argument in this paper is that “public trust” is critical for developing and maintaining the health and wellbeing of individuals, communities, and societies. I argue that public health practitioners and policy makers need to take “public trust” seriously if they intend to improve both the public’s health and the engagement between members of the public and public health systems. Public health practitioners implement a range of services and interventions aimed at improving health but implicit a requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 72 publications
3
67
0
2
Order By: Relevance
“…In contrast to patients and dentists, the advantage of trust in dentist‐patient relationships for the oral health system was less reported owing to the nature of the topic – trust in interpersonal relationships, rather than in the institutional system . Despite different levels of trust –interpersonal vs. institutional (14) – the public health system should draw on trust in clinicians for two reasons: benefits flowing from the interpersonal trust and the role of interpersonal trust as a representation of trust in the healthcare system (5, 40). The first is the expectations that patients and clinicians in trustful relationships would contribute to better public health by supporting health promotion and advocacy activities for public health awareness and literacy (41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to patients and dentists, the advantage of trust in dentist‐patient relationships for the oral health system was less reported owing to the nature of the topic – trust in interpersonal relationships, rather than in the institutional system . Despite different levels of trust –interpersonal vs. institutional (14) – the public health system should draw on trust in clinicians for two reasons: benefits flowing from the interpersonal trust and the role of interpersonal trust as a representation of trust in the healthcare system (5, 40). The first is the expectations that patients and clinicians in trustful relationships would contribute to better public health by supporting health promotion and advocacy activities for public health awareness and literacy (41).…”
Section: Resultsmentioning
confidence: 99%
“…Water fluoridation has also been challenged in some regional areas despite over 70 yr of its effective implementation and a body of evidence for it reducing dental caries (4). Among diverse reasons for the concerns, the lack of trust in healthcare seems to be one of the central factors (5). Not only are public healthcare schemes facing issues of mistrust, but clinical encounters are also experiencing similar problems.…”
mentioning
confidence: 99%
“…It is equally important, however, to use these data and algorithms in a responsible manner, in compliance with data-protection regulations and with due respect for privacy and confidentiality. Failing to do so will undermine public trust, which will make people less likely to follow public-health advice or recommendations and more likely to have poorer health outcomes 10 .…”
Section: Marcello Ienca and Effy Vayenamentioning
confidence: 99%
“…Two types of trust are at play: interpersonal and institutional trust. Interpersonal trust can be defined a mutual confidence that no party will exploit anothers' vulnerability, and an acceptance of the risks associated with the type and depth of the interdependence inherent in a given relationship (43). Interpersonal trust can be developed in face-to-face encounters which involve vulnerability or information asymmetry, dependency, and uncertainty.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…In the Danish CRC screening program using FIT, participation relies on institutional trust, since no face-to-face encounters take place with a HCP in the invitational procedure, in the collection of the screening sample, or in the provision of the screening result. It has been suggested that participation in CRC screening using self-sampling requires a larger 'leap of faith' for participants due to deficits in knowledge and lack of familiarity with the procedure, and most importantly a lack of access point, in the shape of a trusted HCP who can mediate between the institution (screening) and the individual (43).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%